OP0293 A FIRST-IN-CLASS METABOLIC REPROGRAMMING AGENT, MBS2320, SELECTIVELY MODULATES IMMUNE CELL FUNCTION AND IMPROVES OSTEOID FORMATION AND BONE PROTECTION VERSUS ETANERCEPT IN THE MOUSE COLLAGEN-INDUCED ARTHRITIS MODEL. (June 2019) - Patel, Lisa; Foster, Martyn; Shen, Fang; Vink, Paul; Anderson, Ian; Jopling, Louise; Smith, Stephen; Greig, Iain; Williams, Sam
Abstract : Background: Despite the availability of several treatment options, some Rheumatoid Arthritis (RA) patients do not reach low disease activity. There thus remains a need for differentiated new therapies. Prior studies identified a series of biphenylsulphonamides with bone protecting and anti-inflammatory activity 1, 2 which might meet this need. Objectives: To evaluate the selectivity of a novel small molecule, MBS2320, in myeloid and lymphoid cells, characterise its selectivity for osteoclasts versus osteoblasts and characterise its effects on synovitis and osteoprotection compared to an anti-TNFα agent in a therapeutically administered collagen-induced arthritis (CIA) mouse model. Methods: Viability, proliferation or cytokine production were assessed in human primary monocytes, lymphocytes or a Mixed Lymphocytes Reaction (MLR). Human primary osteoclasts (OCs) were differentiated from CD14+ monocytes with M-CSF and RANK–L. Mature OCs were stained with tartrate-resistant acid phosphatase (TRAP) and quantified by light microscopy. Osteolytic activity was assessed on mineral-coated surfaces. Osteoblasts were derived from mesenchymal stem cells by differentiation in the presence of MBS2320; mineralisation was assessed by Alizarin Red S staining. CIA was induced in DBA/1J mice by collagen immunisation. MBS2320 and etanercept were dosed once daily after onset of disease. Arthritic Index (AI) was scored throughout the dosing period after which serial paw sections were assessed for inflammation, synovitis, stromal cavity osteolysis, pannus hyperplasia, osteoid layering and bone resorption foci. Results: MBS2320 reduced the production of cytokine from monocytes and inhibited T-cell proliferation, and cytokine production in a MLR. MBS2320 also reduced primary OC differentiation and function in vitro to a greater degree than alendronate but showed no effect on the differentiation of primary osteoblasts. MBS2320 (0.3 mpk/d) and etanercept (10 mpk/d) inhibited the onset and severity of CIA arthropathy, and synovitis, pannus infiltration and osteolysis, with equivalent efficacy. In addition MBS2320 showed anatomically appropriate osteoid layering with conservation of the tide mark, and the bone marrow showed no cell atypia, with all progenitor classes present although reduced in number and distribution. In contrast, osteoid formation in the etanercept group was multi-focal with an often erratic tide-mark morphology and was localised to areas of reduced osteoclastic resorption and osteolysis with erratic osteocyte distribution. Conclusion: MBS2320 selectively inhibits myeloid and lymphoid activity/differentiation, whilst sparing mesenchymal cells, in vitro. In murine CIA, MBS2320 treatment led to the formation of anatomically appropriate osteoid layering indicating an ongoing process of osteogenesis conditioned by biomechanics. By contrast osteoid formation due to etanercept was more 'reactive' and secondary to suppression of inflammation. The data suggest that MBS2320 offers equivalent anti-inflammatory activity, but a broader spectrum of osteoprotective efficacy in CIA compared to TNFα inhibition and may offer an alternative therapeutic approach to improving bone quality in RA. References: [1] Greig IR, et al. Development and Characterization of Biphenylsulfonamides as Novel Inhibitors of Bone Resorption J Med Chem 2006;49:7487-7492 [2] Coste E, et al. Identification of small molecule inhibitors of RANKL and TNF signaling as anti-inflammatory and antiresorptive agents in mice Ann Rheum Dis 2015;74:220–6 Disclosure of Interests: Lisa Patel Shareholder of: Shareholder of Istesso Ltd, Employee of: Employee of Istesso, Martyn Foster Shareholder of: AstraZeneca, Consultant for: Istesso, Levicept, Employee of: AstraZeneca, Fang Shen Shareholder of: Johnson & Johnson, Employee of: Johnson & Johnson, Paul Vink Employee of: Johnson & Johnson, Ian Anderson Shareholder of: Johnson & Johnson, Employee of: Janssen Research & Development, LLC, Louise Jopling Shareholder of: Johnson and Johnson (employee), Employee of: Employee of Janssen (Pharmaceutical arm of Johnson & Johnson) since May 2008 to present day, Stephen Smith Shareholder of: Istesso Ltd, Consultant for: Istesso Ltd, Iain Greig Shareholder of: Shareholder in OsteoRx Ltd, a spin-out company from the University of Aberdeen, which retains a financial interest in MBS2133, Sam Williams Shareholder of: Shareholders of Istesso Ltd, Employee of: Employees of Istesso